Carbon nanotubes influenced indium oxide as photoanode for dye-sensitized solar cell - Mahalingam S.; Abdullah H.; Manap A. (Korean Society of Mechanical Engineers, 2023)
Crystallite size; Dye-sensitized solar cells; Efficiency; Morphology; Multiwalled carbon nanotubes (MWCN); Nanotubes; Open circuit voltage; Single-walled carbon nanotubes (SWCN); Sol-gel process; Sol-gels; Thin films; Body-centered-cubic phase; Higher efficiency; Large surface area; Morphology analysis; Photocurrent density; Photovoltaic performance; Power conversion efficiencies; Single-walled carbon nanotube (SWCNTs); Indium compounds